A Literature Review of Studies on Addiction-Related Nursing Research Published in Korea from 2010-2020 - Park, Min-Hee (Advances in Social Sciences Research Journal, 2020)
A literature review was conducted to explore the trends in studies on addiction-related nursing research. The study examined articles that had both ‘addiction’ and ‘nursing’ as key words and were published in the period of 2010-2020 in major Korean nursing and health-related journals. Fifteen articles suitable for literature review were analysed. The majority of the articles were on smartphone addiction. With regards to study design, two qualitative studies were conducted to analyse subjects’ experiences, and 13 correlation studies were conducted to analyse relationships between variables. Future addiction-related nursing research should include intervention studies to verify the effectiveness of variables.